A low-carbon high inulin diet improves intestinal mucosal barrier function and immunity against infectious diseases in goats - Yuan, Chunmei; Wang, Shuiping; Gebeyew, Kefyalew; Yang, Xin; Tang, Shaoxun; Zhou, Chuanshe; Khan, Nazir Ahmad; Tan, Zhiliang; Liu, Yong (Frontiers in Veterinary Science, 2023)
Abrupt weaning is a major stressful event, contributing to intestinal abnormalities and immune system dysfunction in weaned kids. Inulin is a prebiotic fiber with many positive functions, including promoting intestinal fermentation and enhancing host immunity in monogastric animals. However, the effects of a high-inulin, energy-rich diet on ruminal fermentation characteristics, methane emission, growth performance, and immune systems of weaned kids have not been investigated. A fully automated in vitro fermentation system was used to investigate ruminal fermentation characteristics and methane emission of a mixed substrate of inulin and fat powder (1.31: 1) in comparison with maize grain-based starter concentrate. During a 1-week adaptation and 4-week trial phase, 18 weaned kids (8.97 ± 0.19 kg) were randomly assigned to two groups, one with a conventional diet (83% maize grain; CON) and the other with a low-carbon, high-inulin diet (41.5% maize grain, 14.4% fat powder, 18.9% inulin; INU). In the in vitro rumen fermentation experiment, the total gas production was not different (p > 0.05); however, a lower (p < 0.05) methane production was observed for INU as compared to CON. The average daily gain and the ratio of feed intake and growth performance of kids fed with INU were higher (p < 0.05) than those fed with CON. Serum concentrations of alanine transaminase (ALT) and lactate dehydrogenase (LDH) were lower (p < 0.05), whereas the concentration of high-density lipoprotein (HDL) and cholesterol (CHOL) were higher (p < 0.05) in kids fed with the INU diet as compared CON. Dietary inulin significantly increased (p < 0.05) the secretion of immunoglobulins (IgA, IgG, and IgM) and inflammatory cytokines (IFN-γ and IL-10) in ileum tissue. Although no differences (p > 0.05) were observed in mRNA expression of tight junction markers, the INU diet tended to increase (p = 0.09) gene expression of ribosomal protein S6 kinase beta-1 (P70S6K) in the mammalian target of rapamycin (mTOR) pathway of longissimus dorsi muscle. Our findings highlighted that a low-carbon high-inulin energy-rich diet can be used as a promising strategy to improve gut immunity and growth performance of weaned kids under abrupt weaning stress and reduce methane production.